LEGAL GROUNDS FOR EXTRADITION AS A GUARANTEE OF SECURING THE RIGHTS OF PERSONS - Panova, Oksana; Makoznak, Sofia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is the analysis of international legal acts (international agreements, conventions) regarding extradition and their impact on Ukrainian procedural provisions in this aspect, which will give us an understanding of the extent to which they are the legal basis of extradition; substantiating the legal grounds for extradition as a guarantee of ensuring the rights of persons who have committed a criminal offense. Research methods: a comprehensive analysis of normative legal acts, scientific literature and the practice of applying criminal procedural legislation was used. Results: it is substantiated that international legal agreements, treaties on extradition, ratified by Ukraine, are one of the forms of cooperation between states in the fight against crime. In turn, Conventions, treaties between states and other legal acts on extradition have a separate system of international legal instruments. It is noted that generally recognized international standards in the field of human rights, in particular regarding ensuring the right to life, liberty and personal integrity, to judicial protection, etc., are of fundamental importance when extraditing a person who has committed a criminal offense. It was determined that, to a certain extent, international norms on the extradition of criminals were systematized and reflected in the Criminal Procedure Code of Ukraine, the provisions of which are a guarantee of ensuring the rights of a person subject to extradition. It is international conventions, agreements, treaties between states that are able to impose restrictions both on the extradition procedure and on the question of criminal liability for acts in which there is a political aspect. International norms refuse to extradite a person who left the country for political offenses, for persecution based on his race, religion, nationality. Discussion: the purpose of extradition is to prevent evasion of justice for a crime committed. The analysis of the conventions and the Code of Civil Procedure of Ukraine proved that the legal provisions are exhaustive and are not subject to expansive, arbitrary interpretation.